Molecular Detection of Anaplasmosis in Crossbred Cattle - Bhanot, Vandna; Jindal, Naresh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Bovine anaplasmosis is an infectious, non-contagious, tick-borne disease of domestic as well as wild ruminants caused by obligate  intraerythrocytic parasites of family Anaplasmataceae and genus Anaplasma. Fifty blood samples were collected from crossbred cattle  in a dairy farm with a history of a drastic decrease in milk yield and fever in a few animals. Six (12%) samples showed characteristic  Anaplasma organisms when stained with Giemsa's stain, whereas 19 (38%) samples were found positive for A. marginale by PCR assay.  Low hemoglobin and total erythrocyte count were observed, whereas an increase in total leucocyte count was noted in Anaplasma affected animals compared to healthy animals at the same farm.
Keywords: Anaplasmosis; Cattle; Hematology; Molecular diagnosis; PCR